Strategy for Application of Risk Management on the Implementation of Renstra - Hasyim Asyari; Zahrotul Munawwaroh; Taufani Chusnul Kurniatun; Nur Aedi (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2018)
AbstractOne of the problems is the low quality of education due to the lack of maximum education institutions in managing the risks that occur in the process of implementing education. The purpose of this study is to find out and obtain data on risk management analysis and what risks faced by Development Madrasah Ibtidaiyah (Elementary School) Pembangunan (MIP) in the implementation of the 2011-2012 Renstra. Through interviews and observations that are known the main subject is a person or group of people who can provide information, they consist of management managers, management leaders to the strategic management staff. This study uses Descriptive Qualitative Analysis Method, to collect data, direct observation at the relevant institution (UIN Syarif Hidayatullah Jakarta). The results of this study explain that Madrasah Ibtidaiyah Pembangunan (MIP) belongs to the risk averter, term namely the people who are reluctant to risk. The risk management stages carried out are risk identification (internal analysis, external and SWOT analysis), risk measurement (cross-linking SWOT, ST, WT, SO, and WO analysis), risk control (risk mitigation, risk retention, risk advoidance and risk risk transfer) and risk evaluation (consortium meetings, education unit meetings, leadership meetings and management review meetings).AbstrakSalah satu masalah rendahnya kualitas pendidikan karena kurangnya lembaga pendidikan yang maksimal dalam mengelola risiko yang terjadi dalam proses penyelenggaraan pendidikan. Tujuan penelitian ini adalah untuk mengetahui dan memperoleh data tentang analisis manajemen risiko dan risiko apa yang dihadapi oleh Madrasah Ibtidaiyah Pembangunan (MIP) dalam pelaksanaan Renstra 2011-2012. Melalui wawancara dan observasi yang diketahui subjek utama adalah orang atau sekelompok orang yang dapat memberikan informasi, mereka terdiri dari manajer manajemen, pimpinan manajemen hingga staf manajemen strategis. Penelitian ini menggunakan Metode Analisis Kualitatif Deskriptif, untuk mengumpulkan data, observasi langsung di instansi terkait (Madrasah Pembangunan UIN Syarif Hidayatullah Jakarta). Hasil penelitian ini menjelaskan bahwa MIP memiliki risk averter, yaitu istilah orang yang enggan mengambil risiko. Tahapan manajemen risiko yang dilakukan adalah identifikasi risiko (analisis internal, analisis eksternal dan SWOT), pengukuran risiko (analisis SWOT, ST, WT, SO, dan WO), pengendalian risiko (risk mitigation, risk retention, risk advoidance and risk risk transfer) dan evaluasi risiko (pertemuan konsorsium, pertemuan unit pendidikan, rapat pimpinan dan rapat tinjauan manajemen).How to Cite : Asy'ari, H., Munawwaroh, Z., Salwa. (2018). Strategy for Application of Risk Management on the Implementation of Renstra. TARBIYA: Journal of Education in Muslim Society, 5(1), 57-65. doi:10.15408/tjems.v5i1.9528.